2014
DOI: 10.5511/plantbiotechnology.14.0731a
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulators of flavonoid biosynthesis and their application to flower color modification in Japanese gentians

Abstract: Japanese cultivated gentians (Gentiana triflora, G. scabra and their hybrids), some of the most important ornamental flowers in Japan, have vivid blue flowers that accumulate polyacylated anthocyanins such as gentiodelphin. To breed attractive flower colors in Japanese gentians, our research group has been studying the molecular mechanisms that control flower pigmentation. Flavonoids, including anthocyanins, are widely distributed in the plant kingdom and are found in almost all plant organs. Along with longst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…The LBGs comprise dihydroflavonol 4‐reductase ( DFR ), leucoanthocyanidin reductase ( LAR ), anthocyanin synthase ( ANS ), anthocyanidin reductase ( ANR ) and glycosyl transferases ( GT ; Xu et al, 2014). The expression pattern of LBGs is significantly different from that of EBGs , and these genes encode enzymes that synthesize anthocyanins and PAs (Nakatsuka et al, 2014). Meanwhile, the structural genes are directly regulated by the MYB‐bHLH‐WD40 (MBW) complex (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The LBGs comprise dihydroflavonol 4‐reductase ( DFR ), leucoanthocyanidin reductase ( LAR ), anthocyanin synthase ( ANS ), anthocyanidin reductase ( ANR ) and glycosyl transferases ( GT ; Xu et al, 2014). The expression pattern of LBGs is significantly different from that of EBGs , and these genes encode enzymes that synthesize anthocyanins and PAs (Nakatsuka et al, 2014). Meanwhile, the structural genes are directly regulated by the MYB‐bHLH‐WD40 (MBW) complex (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All of the flavonoid biosynthetic structural genes that contribute to gentiodelphin biosynthesis have been identified 7,8 . Furthermore, several transcription factor genes, such as MYB and bHLH , regulating flavonoid biosynthesis have been isolated and characterized 911 . For example, a previous transient expression assay demonstrated that GtMYB3, which belongs to the R2R3MYB family, binds to the promoters of the gentian F3 ′ 5 ′ H and 5/3 ′ AT (5,3′-aromatic acyltransferase) genes to upregulate expression 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The petals of Japanese gentians are vivid blue, which is conferred by the polyacylated anthocyanin gentiodelphin [ 24 ]. The flavonoids of Japanese gentian, the structures of the anthocyanins and flavones, and the biosynthetic structural and regulatory genes associated with these pigments have been well studied [ 25 ]. More recently, we determined the structures of flavones that accumulate in the leaves and flowers of G. triflora and identified a novel glucosyltransferase gene involved in the formation of flavone-glucosides [ 26 ].…”
Section: Introductionmentioning
confidence: 99%